Repurposing agricultural and municipal wastes to supply soil with plant-available phosphorus - Banet, Travis, author; Ippolito, Jim, advisor; Melzer, Suellen, committee member; Paschke, Mark, committee member (Colorado State University. Libraries, 2019)
Inorganic phosphorus (P) is a finite resource used to develop fertilizers, heavily applied in agricultural systems, necessary to maintain global crop yields that satisfy global food security needs. In addition to concerns regarding P availability in coming decades, aquatic ecosystems surrounding agricultural lands are susceptible to environmental degradation triggered by excessive P. We tested the ability of aluminum water treatment residuals (Al-WTR), which are known to efficiently sorb inorganic P, to remove organic P from livestock wastewater and subsequently return sorb P to solution. Results that showed Al-WTR can efficiently sorb organic P and desorb P to solution. A greenhouse study was conducted to validate the effectiveness of organic P laden Al-WTR (Al/O-WTR) for its ability to supply soil with plant-available P when compared to a liquid P amendment by growing spring wheat in two differently textured soils with low P concentrations. Results demonstrated that Al/O-WTR could comparably supply coarse textured soils with plant-available P; however, results showed that liquid P amendment is a superior source of plant-available P in fine textured soils.